Jean-Noël Aletti, God’s Justice in Romans: Keys for Interpreting the Epistle to the Romans (trans. from the French by Peggy Manning Meyer) (Subsidia Biblica 37; Rome: Gregorian & Biblical Press, 2010) - Kowalski, Marcin (The Biblical Annals, 2015)
Book review: Jean-Noël Aletti, God’s Justice in Romans: Keys for Interpreting the Epistle to the Romans (trans. from the French by Peggy Manning Meyer) (Subsidia Biblica 37; Rome: Gregorian & Biblical Press, 2010). Pp. vii, 336. € 27,00. ISBN 978-88-7653-647-2.